Sugar Based Biopolymers in Nanomedicine; New Emerging Era for Cancer Imaging and Therapy - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (BENTHAM SCIENCE PUBL LTD, 2017)
Since last decade, sugar based biopolymers are recognized in nanomedicine as promising materials for cancer imaging and therapy. Their durable, biocompatible and adhesive properties enable the fine tuning of their molecular weights (MW) and their miscellaneous nature makes the molecules acquire various conformations. These in turn provide effective endocytosis by cancer cell membranes that have already been programmed for internalization of different kinds of sugars. Therefore, biocompatible sugar based nanoparticles (SBNPs) are suitable for both cell-selective delivery of drugs and imaging through the human body. Recently, well known sugar-based markers have displayed superior performance to overcome tumor metastasis. Thereby, targeting strategies for cancer cells have been broadened to sugar-based markers as noticed in various clinic phases. In these studies, biopolymers such as chitosan, hyaluronic acid, mannan, dextran, levan, pectin, cyclodextrin, chondroitin sulphate, alginates, amylose and heparin are chemically functionalized and structurally designed as new biocompatible nanoparticles (NPs). The future cancer treatment strategies will mainly comprise of these multifunctional sugar based nanoparticles which combine the therapeutic agents with imaging technologies with the aim of rapid monitoring response to therapies. While each individual imaging and treatment step requires a long time period in effective treatment of diseases, these multifunctional sugar based nanoparticles will have the advantage of rapid detection, right drug efficiency evaluation and immediate interfere opportunity to some important diseases, especially rapidly progressing cancers. In this article, we evaluated synthesis, characterization and applications of main sugar based biopolymers and discussed their great promise in nano-formulations for cancer imaging and therapy. However much should be done and optimized prior to clinical applications of these nano-formulations for an efficient drug treatment without overall toxicity for getting most effective clinical results.
Keywords: Sugar; Biopolymer; Cancer; Imaging; Nanoparticle; Therapy; CONJUGATED CHITOSAN NANOPARTICLES; BETA-CYCLODEXTRIN NANOPARTICLES; SOLID LIPID NANOPARTICLES; IRON-OXIDE NANOPARTICLES; TARGETED DRUG-DELIVERY; ACID-MODIFIED CHITOSAN; HYALURONIC-ACID; IN-VITRO; MOLECULAR-WEIGHT; GENE DELIVERY